1377Did patient blood management guidelines reduce the rate of blood transfusion in pregnancy?. (2nd September 2021) - Baldwin, Heather; Randall, Deborah; Nippita, Tanya; Torvaldsen, Siranda; Patterson, Jillian
Abstract: Background: Concern about increasing transfusion rates, adverse effects and increased costs have led to international efforts to reduce transfusion rates. Australian patient blood management guidelines were first introduced for critical bleeding in 2011, followed by obstetric guidelines in 2015. This study examines obstetric transfusion rates before and after the introduction of the critical bleeding and obstetric guidelines, accounting for pregnancy characteristics and prior trajectories. Methods: Data were obtained from linked birth and hospital records from NSW between January 2002 and December 2017. Changes in raw and risk adjusted transfusion rates over time were investigated using interrupted time series analysis to assess changes in the trend in rate of transfusion among pregnant women with the introduction of each set of guidelines. Sensitivity analysis was performed to identify patterns in the data independently from the interventions. Results: Data for 1, 477, 001 births in NSW from 2002 to 2017 were available for analysis. Preliminary analysis suggests the increasing rate of transfusion from 2002 was flattened after the introduction of the 2011 guidelines, with a significantly decreasing trend observed after the 2015 obstetric guidelines were introduced. Conclusions: Patient blood management guidelines were associated with a reduction in the rate of obstetric transfusion in NSW. Key messages: A focus on patient blood management was associated with an approximately 30% reduction in the transfusion rate, compared to the predicted rate, by the end of the study period. Future work will investigate whether this change in transfusion rates is associated with a change in rates of adverse outcomes.